MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Dila Harum Putri (Departemen Matematika, 2020)
Understanding the concept is a basic ability that must be possessed by students in learning mathematics. Low understanding of mathematical concepts will greatly affect student learning outcomes. The application of the Cooperative learning model Numbered Head Together (NHT) type can be applied as an effort to improve understanding of mathematical consepts. The purpose of this research is to describe theoretically whether the cooperative learning model NHT type can improve students’ understanding of mathematical consepts and how the NHT type cooperative learning model NHT type can improve students’ understanding of mathematical consepts. This type of this research is study of literature where data collection is done by tracing sources related to the topics discussed both from textbooks, journals and other sources. The conclusion of this literature study is theoretically the cooperative learning model NHT type can improve students' understanding of mathematical consepts. The application of NHT learning stages can support learning activities so that it can help improve students' understanding of mathematical consepts which can be seen from the achievement of concept understanding indicators.